问题
解答题
已知数列{an},{bn}满足a1=2,2an=1+anan+1,bn=an-1,数列{bn}的前n项和为Sn,Tn=S2n-Sn. (1)求证:数列{
(2)求证:Tn+1>Tn; (3)求证:当n≥2时,S2n≥
|
答案
(1)由bn=an-1,得an=bn+1,代入2an=1+anan+1,
得2(bn+1)=1+(bn+1)(bn+1+1),
∴bnbn+1+bn+1-bn=0,从而有
-1 bn+1
=1,1 bn
∵b1=a1-1=2-1=1,
∴{
}是首项为1,公差为1的等差数列,1 bn
∴
=n,即bn=1 bn
;(5分)1 n
(2)∵Sn=1+
++1 2
,1 n
∴Tn=S2n-Sn=
+1 n+1
++1 n+2
,1 2n
Tn+1=
+1 n+2
++1 n+3
+1 2n
+1 2n+1
,Tn+1-Tn=1 2n+2
+1 2n+1
-1 2n+2
>1 n+1
+1 2n+2
-1 2n+2
=0,1 n+1
∴Tn+1>Tn;(10分)
(3)∵n≥2,
∴S2n=S2n-S2n-1+S2n-1-S2n-2++S2-S1+S1
=T2n-1+T2n-2+…+T2+T1+S1.
由(2)知T2n-1≥T2n-2≥…≥T2≥T1≥S1,
∵T1=
,S1=1,T2=1 2
,7 12
∴S2n=T2n-1+T2n-2+…+T2+T1+S1
≥(n-1)T2+T1+S1=
(n-1)+7 12
+1=1 2
.(16分)7n+11 12